2011
DOI: 10.1186/1749-8090-6-82
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endoscopic vein extraction on structural and functional viability of saphenous vein endothelium

Abstract: ObjectivesEndothelial injury during harvest influences graft patency post CABG. We have previously shown that endoscopic harvest causes structural and functional damage to the saphenous vein (SV) endothelium. However, causes of such injury may depend on the extraction technique. In order to assess this supposition, we evaluated the effect of VirtuoSaph endoscopic SV harvesting technique (VsEVH) on structural and functional viability of SV endothelium using multiphoton imaging, biochemical and immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…19 Furthermore, endothelial injury leads to enhanced medial smooth muscle proliferation and migration, as well as activation of a cascade of mediators governing inflammation and oxidative stress, resulting in accelerated intimal hyperplasia. 1, 22–24 In this investigation, storage in all solutions except autologous whole blood and GALA led to a decrease in endothelial-dependent relaxation compared to UP control. Autologous whole blood preservation exposed the fragile endothelium to a minimally perturbed microenvironment where it was exposed to the same composition of growth factors, proteins and electrolytes as in vivo .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…19 Furthermore, endothelial injury leads to enhanced medial smooth muscle proliferation and migration, as well as activation of a cascade of mediators governing inflammation and oxidative stress, resulting in accelerated intimal hyperplasia. 1, 22–24 In this investigation, storage in all solutions except autologous whole blood and GALA led to a decrease in endothelial-dependent relaxation compared to UP control. Autologous whole blood preservation exposed the fragile endothelium to a minimally perturbed microenvironment where it was exposed to the same composition of growth factors, proteins and electrolytes as in vivo .…”
Section: Discussionmentioning
confidence: 61%
“…1 During typical intraoperative preparation, HSV is subject to a series of “back-table” manipulations. One such manipulation is preservation in a storage medium prior to implantation.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that this oedema may be due to partial interruption of lymphatic drainage due to the long incision needed to harvest the vein in the OVH group. Injection preparations of lower extremity have shown that the superficial lymphatics run in a narrow band of adipose tissue overlying the great saphenous vein and do not communicate with the deep lymphatics [10]. Although EVH does not prevent development of lower extremity oedema, lack of incisions in an edematous leg with obstructed lymphatics may play a role in preventing localized wound dehiscence and cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative risk factors normally associated with leg wound complications include female gender, diabetes mellitus, obesity, hypoalbuminemia, anaemia, peripheral vascular disease, chronic ischemia and steroid use [9,10]. The cause of wound complications and more importantly infections is not completely understood [6].…”
Section: Discussionmentioning
confidence: 99%
“…They found that western blots, immunofluorescent, multiphoton imaging had no difference for caveolin 1, eNOS, Cadherin, and vWf between EVH and OVH [13]. …”
Section: Discussionmentioning
confidence: 99%